2021
DOI: 10.9734/ajee/2021/v15i430234
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Land Use and Land Cover Change of Forest Ecosystems of Shendurney Wildlife Sanctuary, Western Ghats, India

Abstract: Understanding forest degradation due to human and natural phenomena is crucial to conserving and managing remnant forest resources. However, forest ecosystem assessment over a large and remote area is usually complex and arduous. The present study on land use and land cover change detection of the Shendurney Wildlife Sanctuary forest ecosystems was carried out to utilize the potential application of remote sensing (RS) and geographic information system (GIS). Moreover, to understand the trend in the forest eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…
Globally, researchers have extensively studied the changes in Land use/ Land cover (LULC) using Remote Sensing (RS) and Geographical Information System (GIS) and have concluded that LULC must be conducted regularly (Annayat et al 2022;Lodhi et al 2014). Understanding LULC of a particular area, more unfortunately so, if a protected area, is an important question for holistic management and the locals living in proximity (Mutanga et al 2015;Bilyaminu et al 2021). With the application of remote sensing, it has been made possible to study the patterns of changes in land use/land cover at low cost, less time and high accuracy (Kachhwaha 1985).
…”
mentioning
confidence: 99%
“…
Globally, researchers have extensively studied the changes in Land use/ Land cover (LULC) using Remote Sensing (RS) and Geographical Information System (GIS) and have concluded that LULC must be conducted regularly (Annayat et al 2022;Lodhi et al 2014). Understanding LULC of a particular area, more unfortunately so, if a protected area, is an important question for holistic management and the locals living in proximity (Mutanga et al 2015;Bilyaminu et al 2021). With the application of remote sensing, it has been made possible to study the patterns of changes in land use/land cover at low cost, less time and high accuracy (Kachhwaha 1985).
…”
mentioning
confidence: 99%